Coincidence, Probability, Cognitive Error - Szymanek, Krzysztof (Folia Philosophica, 2016)
A lot has been written about coincidence, including research into the probabilistic, methodological, psychological and philosophical aspects of coincidence This paper presents some aspects of the role of coincidence in the human cognitive system, focusing in particular on probabilistic reasoning and logical and methodological errors in reasoning associated with the perception and interpretation of coincidence. Due to the nature of things, it is not possible to omit the areas of research mentioned above.